2021
DOI: 10.1099/jmm.0.001303
|View full text |Cite
|
Sign up to set email alerts
|

Citrobacter koseri stimulates dendritic cells to induce IL-33 expression via abundant ATP production

Abstract: Introduction. Food allergies (FAs) occur due to intestinal immune dysfunction elicited by dysbiotic conditions. It was previously determined by us that Citrobacter species propagate in the faeces of mice with FAs and worsen allergic symptoms by inducing the allergenic cytokine IL-33. Dendritic cells can play important roles in regulation of FA responses. Hypothesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…Consistently, Kataoka et al reported that ATP induced IL-33 expression by stimulating the P2X7 receptor under conditions of GNB infection. 68 Another study also reported that the P2X7 receptor was involved in IL-33 production by increasing the concentration of Ca 2+ . 62 Whether P2X7 can regulate any transcription factor that induces IL-33 expression, such as CDX2, remains unclear.…”
Section: Discussionmentioning
confidence: 97%
“…Consistently, Kataoka et al reported that ATP induced IL-33 expression by stimulating the P2X7 receptor under conditions of GNB infection. 68 Another study also reported that the P2X7 receptor was involved in IL-33 production by increasing the concentration of Ca 2+ . 62 Whether P2X7 can regulate any transcription factor that induces IL-33 expression, such as CDX2, remains unclear.…”
Section: Discussionmentioning
confidence: 97%
“…Citrobacter has been identi ed as a microorganism that can cause intestinal in ammation; thus, Citrobacter rodentium is inextricably linked to human immune cells, especially dendritic cells and CD4+ T cells 26 . Citrobacter koseri, a subspecies of Citrobacter, stimulates dendritic cells to induce IL-33 through massive ATP production 27 . Plasmacytoid dendritic cells (pDCs) are the main dendritic cells upregulated upon stimulation in Citrobacter rodentium infection 28 .…”
Section: Discussionmentioning
confidence: 99%
“…There were eleven GI infection models undertaken in mice ( Heiss et al, 2008 ; Keating et al, 2011 ; Coquenlorge et al, 2014 ; Miller et al, 2015 ; Huang et al, 2017 ; Shimokawa et al, 2017 ; Liu et al, 2018 ; Stark et al, 2018 ; Guan et al, 2021 ; Kataoka et al, 2021 ), human fetal small intestinal epithelial cells (FHs 74 Int cells) ( Quan et al, 2018 ), human liver and spleen cell samples ( Stark et al, 2018 ), human longitudinal muscle-myenteric plexus ( Coquenlorge et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Infective agents used included T. gondii ( Miller et al, 2015 ; Huang et al, 2017 ; Quan et al, 2018 ), T. spiralis ( Keating et al, 2011 ; Huang et al, 2017 ; Guan et al, 2021 ), Heligmosomoides polygyrus (Hp) ( Shimokawa et al, 2017 ), lymphocytic choriomeningitis (LCMV) ( Stark et al, 2018 ), C. difficile ( Liu et al, 2018 ), C. koseri ( Kataoka et al, 2021 ), L. monocytogenes ( Heiss et al, 2008 ), and LPS from E. coli and Salmonella typhosa ( Coquenlorge et al, 2014 ). Modes of administration included orally ( Heiss et al, 2008 ; Keating et al, 2011 ; Miller et al, 2015 ; Huang et al, 2017 ; Shimokawa et al, 2017 ; Stark et al, 2018 ) or intraperitoneally ( Stark et al, 2018 ) for in vivo murine models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation